Impact of Attitude Category on Problem-Solving Skills: An Experiment within a Flipped Learning Model with STEM Approach - Rusnilawati, Rusnilawati; Ali, Siti Rahaimah Binti; Hanapi, Mazarul Hasan Mohamad (Universitas Muhammadiyah Surakarta, 2023)
This research endeavours to elucidate the notable disparities in Problem-Solving Skills (PSS) when employing the Flipped Learning Model with a STEM Approach (FLM-SA) in contrast to Routine Learning, contingent upon attitude categories. The study harnesses a quantitative methodology with a quasi-experimental design. A sample size of 210 students is utilised, chosen via cluster random sampling. The instruments for data collection comprise: 1) an attitude questionnaire; 2) problem-solving tests; and 3) an observation sheet for the execution of the learning process. The techniques for data analysis employed are both parametric and non-parametric tests. The findings unveil a significant discrepancy in the students' Problem-Solving Skills based on attitude category between the control group, post the implementation of routine e-learning, and the treatment group, post the utilisation of the FLM-SA Module. Students possessing a Medium Attitude Category in the experimental class exhibit superior problem-solving skills compared to the control class. In contrast, students with Low and High Attitude Categories do not demonstrate a significant difference between the control and experimental classes. These findings underscore the significance of differentiated learning by implementing Teaching at the Right Level. Ideally, teachers should conduct an initial diagnostic assessment to ascertain students' initial attitudes or abilities